Concentration, Standing State and Cycling of Calcium in Soil-vegetation Components in Sand Dune Regions around Pilani, Rajasthan - Singh, Room; Joshi, M C (Annals of Arid Zone, 2016)
The concentration, standing state and cycling of calcium in the herbaceous vegetation in sand dune ecosystems at Narhar near Pilani (28Â° 37' N. 75Â°. 37 E, 350 m) were studied between June 1973 to May, 1974. Four sand dune sites (Site I-windward, Site II-top, Site Ill-leeward and Site IV-interdunal lows) were compared with site V (exclosure). The concentration (%) in different vegetational components and in soil (30 cm depth) fluctuated in different sites and months. The amount of calcium also showed wide seasonal and interseasonal fluctuations on all the sites throughout the study. The uptake storage and transfer and release were similar on all the sites with a slight variation. The uptake was maximum in rainy season. However, transfer was more during winter and summer seasons. Only 1-2% of the total calcium was involved in biological circulation while a major portion (98-99%) remained in the soil. Of the total calcium absorbed by roots, 79%,62%,80%,79% and 87% were returned to the soil in sites I-V, respectively.